Pesticide Interactions - Frederick M. Fishel (EDIS)
PI-145, a 3-page illustrated fact sheet by Frederick M. Fishel, describes the types of interactions that can occur when pesticides are mixed and applied with other agricultural chemicals. Examples of typical incompatibilities and interactions are provided. Published by the UF Pesticide Information Office, April 2007.